2009
DOI: 10.1186/1471-2458-9-268
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and changes in chronic diseases among South Korean farmers: 1998 to 2005

Abstract: BackgroundEpidemiologic studies have suggested a unique pattern of disease among farmers in Western countries, but limited information is available about the magnitude of disease prevalence and their changes over time in Asian farmers. The aim of this study was to compare the prevalence and changes in chronic diseases among farmers with those of other occupational groups in South Korea.MethodsUsing data from three consecutive cross-sectional national surveys: the Korean National Health and Nutrition Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(32 reference statements)
1
10
0
2
Order By: Relevance
“…Researchers also have begun to analyze joint disease by geographical context and, consistent with our results, have found that rural areas exhibit higher levels of joint disorders [2,42,43]. Joint conditions have been associated with contextual factors including pollutants, mechanical factors affecting the hands (e.g., occupational load), poverty and low education [44][45][46].…”
Section: Discussionsupporting
confidence: 84%
“…Researchers also have begun to analyze joint disease by geographical context and, consistent with our results, have found that rural areas exhibit higher levels of joint disorders [2,42,43]. Joint conditions have been associated with contextual factors including pollutants, mechanical factors affecting the hands (e.g., occupational load), poverty and low education [44][45][46].…”
Section: Discussionsupporting
confidence: 84%
“…Os fatores de risco para as atividades não agrícolas, principalmente de áreas urbanas, incluem a inatividade física, esforço repetitivo, sobrecarga psíquica, entre outros (MENDES, 1988). Estudos sugerem, por exemplo, que a prevalência de doenças músculo-esqueléticas é maior entre os trabalhadores agrícolas comparativamente a outras ocupações, em função da má postura e outras condições inadequadas de trabalho a que estão submetidos esses trabalhadores (CHA et al, 2009). As doenças respiratórias também seriam mais frequentes em trabalhadores agrícolas quando o uso de pesticidas é comum no trabalho (CHAKRABORTY et al, 2009).…”
Section: Introductionunclassified
“…17,21 Farmers were found to have a higher prevalence of arthritis, intervertebral disc disorders, and gastritis compared to other workers and the total Korean population. Farmers had a lower prevalence of hypertension, asthma, cancer, diabetes, chronic hepatitis, and chronic obstructive pulmonary disease, and a similar prevalence of cerebrovascular disease, ischemic heart disease, tuberculosis, and cataracts/glaucoma compared to the total Korean population.…”
Section: Current Status Of Agricultural Health and Safety In Koreamentioning
confidence: 94%
“…As such, little is known about occupational health and safety conditions in the Korean agricultural sector. 17 A few surveys have been conducted that provide hints to the magnitude of illness and injury among farmers and rural residents. A survey conducted in 2008 of a representative sample of 4809 rural households (consisting of 9630 household members) found that the annual rate of work-related injuries involving at least 4 hours away from work was 5.6%.…”
Section: Current Status Of Agricultural Health and Safety In Koreamentioning
confidence: 99%